2008
DOI: 10.1086/589742
|View full text |Cite
|
Sign up to set email alerts
|

The Kinematics of a Globally Propagating Disturbance in the Solar Corona

Abstract: The kinematics of a globally propagating disturbance (also known as an ``EIT wave") is discussed using Extreme UltraViolet Imager (EUVI) data Solar Terrestrial Relations Observatory (STEREO). We show for the first time that an impulsively generated propagating disturbance has similar kinematics in all four EUVI passbands (304, 171, 195, and 284 A). In the 304 A passband the disturbance shows a velocity peak of 238+/-20 kms-1 within ~28 minutes of its launch, varying in acceleration from 76 ms-2 to -102 ms-2. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
181
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(202 citation statements)
references
References 25 publications
(28 reference statements)
21
181
0
Order By: Relevance
“…This was first observed for a coronal EUV wave by Long et al (2008) and Veronig et al (2008), and studied in detail by Gopalswamy et al (2009). The reflected wave was clearly seen in difference images and in intensity profile stack plots (see Figure 30).…”
Section: Reflectionmentioning
confidence: 62%
See 3 more Smart Citations
“…This was first observed for a coronal EUV wave by Long et al (2008) and Veronig et al (2008), and studied in detail by Gopalswamy et al (2009). The reflected wave was clearly seen in difference images and in intensity profile stack plots (see Figure 30).…”
Section: Reflectionmentioning
confidence: 62%
“…With STEREO/EUVI, wavefronts could be seen for the same event in all three of these channels (Long et al, 2008;Veronig et al, 2008), plus in 304Å images, where the fronts are comparatively faint and diffuse. These observations have confirmed earlier multiwavelength studies that clearly showed that coronal wave are multithermal phenomena.…”
Section: Thermal Characteristicsmentioning
confidence: 85%
See 2 more Smart Citations
“…The inset at bottom right shows the velocity as a function of time from Hα (crosses) and EIT (circles). Veronig et al 2008;Long et al 2008). Using two events observed in EIT 195Å supplemented by Hα images, Warmuth et al (2001) reported a non-linear velocity profile, implying a non-zero acceleration for the disturbance for at least the first ≤2000 s of the observations.…”
Section: V(t)mentioning
confidence: 98%